Kajian Pengelolaan Sampah Berbasis Masyarakat dengan Konsep 3R (Reduce, Reuse, Recycle) di Kelurahan Larangan Kota Cirebon - Puspitawati, Yuni; Rahdriawan, Mardwi (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2012)
The community based waste management with 3R concept (reduce, reuse, recycle) carried out by the people in Larangan Sub-district in Cirebon city has shown great potential for replication in other places, posing the need for an in depth study on its successful implementation. The study identifies community’s social character and participation capacity in waste management. It analyzes community’s perception of the benefits of waste management in terms of public health, economics and psychology. The study employs qualitative approach by case study to comprehensively describe the social interaction taking place in the community’s based waste management. The study showed that the community’s social and cultural characters have more influence in the activity compared to its socio-economic character. Participation is bottom-up, starting from the identification of problems/needs by the people up to collective experience of benefits. The process begins with community empowerment through capacity building of social characteristics by the RW 08 Merbabu Asih administrations. The activity not only increases the neighborhoods quality of environment and life, it has also changed the people’s behavior in reducing waste, turning involvement in waste management a part of the daily life culture.